Manipulating the light-matter interactions in plasmonic nanocavities at 1 nm spatial resolution - Bao-Ying Wen; Jing-Yu Wang; Tai-Long Shen; Zhen-Wei Zhu; Peng-Cheng Guan; Jia-Sheng Lin; Wei Peng; Wei-Wei Cai; Huaizhou Jin; Qing-Chi Xu; Zhi-Lin Yang; Zhong-Qun Tian; et al. (Light: Science & Applications, 2022)
The plasmon-exciton interaction between gap-mode nanocavities and A excitons of MoS2 is investigated, and the longitudinal distribution of the plasmon-exciton interactions is obtained at ~1 nm spatial resolution.